MOLECULAR DYNAMICS SIMULATION OF THE CH4 AND CH4-H2O SYSTEMS UP TO 10 GPA AND 2573 K - Zhang C.; Duan Z.; Zhang Z. (My University, 2007)
Based on our previous study of the intermolecular potential for pure H 2 O and the strict evaluation of the competitive potential models for pure CH 4 and the ab initio fitting potential surface across CH4 –H2O molecules in this study, we carried out more than two thousand molecular dynamics simulations for the PVTx properties of pure CH 4 and the CH4 –H2O mixtures up to 2573 K and 10 GPa. Comparison of 1941 simulations with experimental PVT data for pure CH 4 shows an average deviation of 0.96% and a maximum deviation of 2.82%. The comparison of the results of 519 simulations of the mixtures with the experimental measurements reveals that the PVTx properties of the CH 4–H 2O mixtures generally agree with the extensive experimental data with an average deviation of 0.83% and 4% in maximum, which is equivalent to the experimental uncertainty. Moreover, the maximum deviation between the experimental data and the simulation results decreases to about 2% as temperature and pressure increase, indicating that the high accuracy of the simulation is well retained in the high temperature and pressure region. After the validation of the simulation method and the intermolecular potential models, we systematically simulated the PVTx properties of this binary system from 673 K and 0.05 GPa to 2573 K and 10 GPa. In order to integrate all the simulation results and the experimental data for the calculation of thermodynamic properties, an equation of state (EOS) is developed for the CH 4–H2 O system covering 673–2573 K and 0.01–10 GPa. Isochores for compositions <4 mol% CH 4 up to 773 K and 600 MPa are also determined in this paper. The program for the EOS can be downloaded from www.geochem-model.org/programs.htm.